Perbedaan Abnormal Return Saham Sebelum dan Sesudah dilakukan Artificial Intelligence (AI) pada Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia - Ningtias, Kiki Arista Wahyu; Supeni, Retno Endah; Sari, Maheni Ika (Universitas Muhammadiyah Magelang, 2024)
The purpose of this study was to determine any abnormal returns before and after the development of artificial intelligence which was listed on the Indonesian Stock Exchange. This research uses an event study which studies market reactions to an event. Event studies are used to test the information content of an announcement. The population used in this research is banking companies listed on the Indonesia Stock Exchange for the period 5 days before and 5 days after 2021-2024. The data used in this research is secondary data and sample selection used purposive sampling. There were 32 companies as samples with a total of 105 initial data. The analytical method used to test the hypothesis in this research uses the paired sample t-test. The results of this research show that artificial intelligence has a significant effect on abnormal returns.